Development of clinical photoacoustic imaging system - Kew, Kok Wen (2016)
Sentinel lymph node biopsy using methylene blue and radioactive tracers has replaced invasive axillary lymph node dissection and become the standard method of axillary staging in planning appropriate treatment and determining prognosis for clinically node-negative breast cancer patients. However, two or more invasive surgical procedures with associated patient morbidity are often required for definitive staging and treatment of the axilla in current sentinel lymph node biopsy practice. To minimize morbidity and expenses potentially associated with extensive surgery in the axilla as part of primary treatment for breast cancer patients, a dual-modality photoacoustic and ultrasonic imaging system has been developed to noninvasively detect sentinel lymph nodes, which most likely contain metastatic cancer cells based on the accumulation of methylene blue dye. Light absorbances in embedded objects at various depths within multilayered tissues were determined by Monte Carlo simulations of light transport in turbid medium to optimize near-infrared laser pulses of 670-nm wavelength delivery for maximum optical penetration. Potential feasibility of laser opto-acoustic imaging for clinical applications was demonstrated by its capability to detect and localize small spherical phantoms with enhanced absorption coefficient relative to the background absorption at a depth of up to 2.5 cm in ex vivo. These results demonstrate the clinical potential of non-invasive opto-acoustic imaging for facile identification of sentinel lymph nodes in cancer staging and metastasis detection with promising diagnostic capability. It was shown that combined photoacoustic tomography and ultrasound potentially allows identification and sampling of the sentinel lymph node using percutaneous fine needle aspiration biopsy, thereby eliminating the need for invasive axillary staging procedures.